Catastrophic healthcare expenditure and coping strategies among patients attending cancer treatment services in Addis Ababa, Ethiopia - Gebremicheal Gebreslassie Kasahun; Gebremedhin Beedemariam Gebretekle; Yohannes Hailemichael; Aynalem Abraha Woldemariam; Teferi Gedif Fenta (BMC, 2020)
Abstract Background With the rapid increase in magnitude and mortality of cancer, which is costly disease to manage, several patients particularly in developing countries are facing a huge financial burden. The study aimed to examine the incidence of catastrophic health expenditure (CHE), identify associated factors and coping strategies among patients attending cancer treatment services in Addis Ababa, Ethiopia. Methods A hospital-based cross-sectional survey of patients with cancer was conducted in public and private hospitals between January and March 2018. Data was collected using a structured questionnaire. All direct medical and nonmedical expenditures were measured and reported as expenditure (US$) per patient (1US$ equivalent to 23.41 Ethiopian Birr). The CHE was estimated using a threshold of 10% of annual household income. Results A total of 352 (response rate of 87.1%) participants were interviewed. Majority (73.3%) of the respondents were females; most (94%) from public hospitals and their mean (±SD) age was 48 ± 13.2 years. Vast majority (74.4%) of patients experienced CHE with mean overall expenditure of $2366 per patient (median: $1708). Medical expenditure shared the highest overall expenditure (83.6%) with mean medical and nonmedical costs of $1978 (median: $1394) and $388 (median: $222), respectively. Patients who took greater than six cycles of chemotherapy (AOR: 3.64; 95% CI: 1.11-11.92), and age (AOR: 1.03; 95% CI: 1.01-1.06) were significantly associated with CHE. Household saving (85.5%) followed by financial support received (43.0%) was the main coping strategy. Conclusion A substantial number of patients with cancer were exposed to CHE with a considerable medical expenditure. Hence, in addition to the popularization of the already introduced health insurance scheme, other better prepayment or insurance mechanisms should also be considered to ensure financial risk protection and realize universal health coverage for patients with cancer.